Faktor- Faktor yang Menyebabkan Kejadian Postpartum Blues - Purwati Purwati; Alfi Noviyana (Jurnal Infokes, 2020)
About 70-80% of postpartum mothers experience mood or feeling disorders. In general, this condition is still considered normal, felt from 2-3 days after delivery and normally disappears after 2 weeks post partum. The purpose of this study was to determine the factors that cause the symptoms of postpartum blues to appear. This research method used qualitative through a phenomenological approach by taking the population by means of purposive sampling. The results showed that age and parity did not always trigger the symptoms of postpartum blues, the causes of postpartum blues were worrying about the baby, maternal fatigue, comments from people around the mother, husband's support and presence, adaptation to the baby's presence.